К ОБОСНОВАНИЮ ОСОБЕННОЙ ЮРИДИЧЕСКОЙ ЛОГИКИ - Бандурка, Олександр Маркович, Тягло Александр Владимирович (SUPREMANCE OF LAW, 2017)
This paper is devoted to explication and comparative analysis of two main approaches to realize the legal logic nature. In accordance with the first realization - trivial - legal logic is reduced to a local application of formal logic in the field of law. Ilmar Tammelo views, unknown to Moldavian and Ukrainian specialists practically, are critically discussed in this connection. The second - nontrivial - realization ascended lineally to G. W von Leibniz.
Keywords: legal logic; formal logic; formal validity; pragmatic validity; Ilmar Tammelo